HIV/AIDS e estilo de vida: parâmetros imunológicos, virológicos, síndrome lipodistrófica e sua relação com a prática de exercícios - Soares, Themis Cristina Mesquita (2012)
This descriptive study aimed to investigate the relationship between expression of immunological (TCD4 +) and virological (viral load) parameters, lipodystrophy syndrome and lifestyle variables of people living with HIV who underwent a program of physicalexercise. Initially, the sample was composed by 17 persons, recorded at the Department of Giselda Trigueiro Hospital Care (GTH), Natal-RN . With the passing of the stages of intervention (physical training program- PTP) the number of participants has changed (17, 9, 8 and 7) as the training phases (I, II, III and IV). Data collected were on total cholesterol, High Density Lipoprotein (HDL) and triglycerides. The % fat (% F), body mass index (BMI), waist-hip ratio (WHR), lean mass (LM), central fat (BF), total (TF) and peripheral (PF), weight and height were used to measure the morphological parameters. For control of variables (TCD4 +, viral load, Triglycerides, Cholesterol, HDL), the information contained in the blood tests every four months were investigated. After Phase I and II, it was used a structured interview. Then sampling was carried out considering the pre-and post-tests 1, 2, 3 and 4 (after 16, 32, 48 and 64 weeks of training, respectively). Daily, the intensity of the work was checked by the scale of perceived exertion for exercises adapted to resistance34. Procedures used were descriptive statistics (dispersion, absolute and relative frequencies, means, standard deviations and minimum and maximum values) as well as Spearman linear correlation adopting a significance level of p ≤ 0.05. Positive changes were observed for TCD4 + and viral load in all phases of the PTP. For the morphological components, the loss of central subcutaneous fat (CSF) and total subcutaneous fat (TSF) for both sexes and the decrease in % BF among women were the most dramatic results after the training phase I. For men, results were more significant to % F and LM in Phases I and II and peripheral subcutaneous fat (PSF) declined in all phases of the exercise. As for women, results were more expressive for % F and TM in the phases I and II and the PSF decreased in all phases of the exercise. Whereas for women, the waist/hip ratio (WCQ) and 0% F decreased and showed a positive association with triglycerides (WHR r * 0.82, p 0.042, r 0.88 TSF *, p 0.019 and r 1.00 ** CSF, p <0.001) and among men with limb subcutaneous fat (LSF)* r 0.65, p 0.029). The PTP provided improvement in the health, self-esteem and quality of life, proving to be a possible strategy to positively influence the expression of immunological parameters (TCD4 +) and virological (viral load) and morphological components of people living with HIV causing no deleterious effects in these parameters